A dog's life - Dubowski, Cathy East. (New York : Pocket Books, 1998)
When Sabrina decides to conjure up some magical help with her baking, her mixing spell goes haywire and she accidently turns Harvey into a dog and his dog into a human.
"Archway paperback.".
"Based on the hit TV series"--Cover.
5.5
3-6
Keywords: Dogs -- Fiction; Witches -- Fiction; Dogs -- Fiction; Witches -- Fiction